Risk, political security and extra-judicial penality under Xi - Li, Enshen (Theoretical criminology, 2023)
In authoritarian regimes, risk tends to be politically positioned to reflect the ruling party's interests, needs and priorities. In this article, I focus on the People's Republic of China (China) as a case study to isolate the issue of risk, and more specifically, analyse why risk is framed as a political tenet, what becomes the evidence of such risk, and how it relates to the country's legal approach to maintaining political stability in the Xi Jinping era. This article critically scrutinizes the latest political dynamics and police practices to argue that China has formulated an extra-judicial penal jurisprudence through what I call ‘forward-leaning’ policing (前倾式警务) against those who are perceived to present a threat of political harm. By using data on 2226 cyber-dissident cases during 2014–2021, my analysis points to this ‘warrior style’ policing being an intensified application of coercive police actions, which is heavily weighted towards incarceration as the main approach to addressing political dissent, especially through administrative detention. In doing so, the judicial process that traditionally determines conviction and sentencing is either circumvented or reduced to symbolic significance.